Characterization of aquifer colloids and dissolved organic matters in KURT granitic groundwater system - Ha, Junhyuk; Lee, Jun-Yeop (Nuclear engineering and technology, 2025)
The natural colloidal particles can facilitate the migration of radionuclides over long distances in deep geologic disposal conditions through adsorption reactions. In the present work, the physicochemical properties of colloidal particles and dissolved organic matters (DOM) contained in the natural groundwater sample, taken from the DB-3 borehole in KAERI (Korea Atomic Energy Research Institute) underground research tunnel, were investigated by using various analytical methods. An airtight cylinder coated on the inside with polytetrafluoroethylene (PTFE) was used for sampling and carrying the DB-3 groundwater sample. Due to the small concentration of colloidal particles in the groundwater, the sample was concentrated by using the tangential flow ultra-filtration (TFUF) system. The components of clay minerals and metal-sulfur compounds at micromolar concentration level were mainly observed through electron microscopy. The colloidal particles with a relatively wide range of sizes were moderately stable under the given aqueous system. Analysis of DOM in the DB-3 groundwater system revealed the predominant presence of low molecular weight (LMW) neutral compounds with functional groups consisting mainly of alkane species. The characteristics of colloidal particles and organic matter in DB-3 groundwater are expected to help understand the migration and retardation behavior of radionuclides in water-conducting fractures of crystalline host rock.